2021
DOI: 10.1016/j.ebiom.2021.103716
|View full text |Cite
|
Sign up to set email alerts
|

Identification of copy number variation-driven molecular subtypes informative for prognosis and treatment in pancreatic adenocarcinoma of a Chinese cohort

Abstract: Background: Pancreatic adenocarcinoma (PAAD) is one of the most lethal carcinomas, and the current histopathological classifications are of limited use in clinical decision-making. There is an unmet need to identify new biomarkers for prognosis-informative molecular subtyping and ultimately for precision medicine. Methods: We profiled genomic alterations for 608 PAAD patients in a Chinese cohort, including somatic mutations, pathogenic germline variants and copy number variations (CNV). Using the CNV informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…DNA extraction and sequencing were performed as previously described with some modifications. [ 27 ] QIAamp DNA Micro Kit (Cat No./ID: 56304) was used to extract genomic DNA from tissue samples, and NanoDrop2000 was used to detect the concentration and purity of DNA. DNA was segmented to a length range of 150–300 bp using Covaris M220 DNA ultrasonic fragmentation instrument.…”
Section: Methodsmentioning
confidence: 99%
“…DNA extraction and sequencing were performed as previously described with some modifications. [ 27 ] QIAamp DNA Micro Kit (Cat No./ID: 56304) was used to extract genomic DNA from tissue samples, and NanoDrop2000 was used to detect the concentration and purity of DNA. DNA was segmented to a length range of 150–300 bp using Covaris M220 DNA ultrasonic fragmentation instrument.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, others have indicated that data that is readily accessible through online repositories has, in some cases, been either poorly formatted or poorly annotated for subsequent analysis 43,44 . In certain instances, this may lead to misguided or misinformed conclusions in well-meaning investigations [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] . Clearly, these challenges pose a major hurdle in the development of novel hypotheses, particularly for those without first-hand familiarity with how the data were generated.…”
Section: Discussionmentioning
confidence: 99%
“…First, validation is frequently only performed on one publicly available dataset. Second, there are multiple examples of inappropriate use of The Cancer Genome Atlas (TCGA) Program PDAC dataset [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] . The mRNA dataset includes 182 samples, but only 150 have been confirmed histologically as PDAC.…”
mentioning
confidence: 99%
“…The presence of chromosomal aberrations is a common molecular feature in human cancer, including loss of tumor suppressor genes or gain of oncogenes, driving oncogenic signaling and cancer development. Specifically, in PC, the amplification of genes involved in DNA repair and tyrosine kinase signaling are associated with poor survival [ 2 ]. The detection of such alterations in cell-free DNA (cfDNA) released from tumor cells (circulating tumor DNA (ctDNA)) has shown promise for several cancers in (pre-) clinical studies [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%